The future of information and communications technology transfer in the Philippine Garments Industry through forecasting by analogy - Pamittan, Rose Anne; Francisco, Emma Cariño (Quezon City University of the Philippines Diliman, 2016)
Few decades ago, the garment is one of the protected traded goods through the MFA quota imposed by the World Bank, Bangladesh and Philippines were two of the many developing countries that took advantage and benefited from this quota system until 2005.

With the likes of China in the game, low labor cost in the case of Bangladesh, and highly skilled workers in the case of the Philippines were not enough to maintain competitiveness in the global garment market. Buyer power is very high that global buyers dictate the trajectory of the market and the requirements of every garment order they put in place. As such, technology is necessary to be in place in the various business processes of these garments companies to ensure that they are integrated with the supply and value chain. Otherwise, there is a high chance that they lose their customers and/or buyers to their competitors who can offer cheaper prices, and faster lead time- benefits brought about by Information and Communications Technologies (ICT) embedded in each company's business process and interlinked to its partners including its buyers and suppliers.

Bangladesh realized this early when three years after the quota lifting, one of the country's biggest garments company incorporated SAP in their full business process. The company acknowledged the fact that the low cost of labor in Bangladesh should be complemented with a system that will ensure speed-to-market of products as well as efficiency in the workforce and in the production. It was also acknowledged that the only way to be linked with global buyers who already stopped using agents or third party companies in their sourcing would be the use of internet and solutions like Enterprise Resource Planning (ERP).

Philippines on the other hand took the other route. Instead of upgrading its garment products in the value chain and integrating various technologies to keep the sector competitive, the government first tried to lobby in the US Congress to pass a bill allowing Philippine-made garments to be exported in the US with reduced tariff. However, this did not push through. The country was not able to maximize and exploit the inclusion of garment products in the Generalized Scheme of Preferences (GSP) awarded by the US and the EU primarily because of the strict Rules of Origin (RoO). This resulted in the decline of the Philippine garment sector from one of the top ten traded products in 2005 to a laggard industry in the present. Just recently, an attached government agency to the Department of Trade and Industry (DTI) called Garments and Textile Industry Office (GTIDO) previously known as Garments and Textile Export Board (GTEB) was abolished and the specific function of this agency was entrusted to the Center for International Trade, Expositions and Missions (CITEM) for garment and textile products' promotion and Department of Science and Technology (DOST) for textile research and development.

With the use of forecasting by analogy, if the domestic Philippine garment sector follows the trend of Bangladesh in growing the sector, then it would require for the government to become proactive in putting in place policies and reforms that will ease the processes of doing business in the country from the importation of raw materials, to customs facilitation, to logistics, and even financial guarantees for the private companies to be more aggressive in incorporating technologies in their production and business processes. The private sector represented by the industry associations and the government should also collaborate to showcase the importance of ICT technologies e.g. ERP solutions to be fully integrated into the global value chain and supply chain of the garment sector. The economic viability of doing business is also important as global buyers will less likely engage with companies located in countries where goods have the tendency to get stuck in customs or undelivered on time due to infrastructure concerns as this defeats the speed-to-market demanded by garment buyers and retailers.

In conclusion, the Philippine garment sector still has a huge potential to be revived and once again capture a sizable market in the global garment industry with the help of ICT in integrating the Philippine garment sector in the global value and supply chain. Garment company owners should realize the cost reduction and lead time reduction that ERP solutions can bring in the business processes and production processes that can be efficiently managed with the use of ERP solutions.

It is also recommended that further studies specifically quantitative analyses in the sector should be done. Also, a foresight activity is a plausible next action to be able to picture different scenarios in the midterm and long term and will contribute to better planning for both the government and the industry.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Technology transfer; Clothing trade -- Philippines; Technological forecasting